KECEMASAN IBU HAMIL TRIMESTER III SETELAH MENONTON VIDEO PERSALINAN NORMAL DAN DIBERIKAN TEKNIK HYPNOBIRTHING - Yessie Sorta Romauli; Sri Sumiati; Taliah Taliah (Poltekkes Kemenkes Bengkulu, 2020)
Abstract : In terms of psychological, anxiety in pregnant women can affect the process of delivery and quality of babies to be born, so if not treated can cause various complications. The best way to overcome that problem is by watching normal birth videos and hypnobirthing techniques. The aim of this research is to know the difference of anxiety of trimester pregnant woman after watching normal delivery video and given hypnobirthing technique. This type of research is quasi experiment with nonequivalent time sample design method. The population used were all primigravida trimester III mothers as many as 30 respondents who divided as many as 15 respondents in Puskesmas Kandang and 15 respondents in working area of Padang Serai Public Health Center. Sampling technique in this study was taken in total sampling. Univariate analysis results obtained the average anxiety before and after watching the birth video is 31.87 and 15.73. The average anxiety before and after given hypnobirthing technique is 32,07 and 26,33. The result of bivariate analysis shows that p-value = 0,000 <0,05, meaning that there is a significant difference on the average anxiety of pregnant mother of trimester III after watching normal delivery video with hypnobirthing technique. Multivariate results obtained p-value> 0.05 means confounding factors in the form of age, education, and work does not affect the anxiety of pregnant women third trimester. It is expected that the puskesmas can work together with health agencies to be able to provide intervention in the form of watching the birth video in order to reduce the anxiety of primigravida mother in preparation for childbirth later.Keywords : Anxiety, Childbirth Video, Hypnobirthing Technique